ANALISIS FAKTOR MUAT SEBAGAI PENYEBAB KETERLAMBATAN KEBERANGKATAN KERETA DI STASIUN PASOSO TANJUNG PRIOK PT. KERETA .docx - Gilbert Alfons; Dadang Suyadi (LOGISTIK, 2018)
PT. Kereta Api Indonesia is an Indonesian state-owned company that provides train transportation services. PT KAI's services include passenger and freight transportation. For freight transport, PT. Kereta Api Indonesia is working with partners to deliver of the goods they have. Partners of PT. Kereta Api Indonesiauses jasa train services so that the goods they are going to send can reach their destination quickly and according to the scheduled time. The cost of sending goods using train services is not cheap. This can make the partners ofPT. Trains Indonesia is changing its mode of transportation such as trucks. To improve and expedite so that train departures are in accordance with the schedule, it is necessary to know the causes of the delay in departing the train. The author conducted an analysis using termination data and conducted interviews with employees who worked at Pasoso Station. From the results of the analysis, the overall delay occurred by 76% and the timeliness of leaving was 24%. The main factor that causes to delay is the long loading process